GEOPHYSICAL ASSESSMENT OF SUBSURFACE CONDITIONS AT PROPOSED BUILDING SITES: IMPLICATIONS FOR FOUNDATION FAILURE AND BUILDING COLLAPSE. - Ariyo, Stephen Oluwafemi; FATOBA, Julius Ogunmola; BAYEWU, Olateju O.; OMOSANYA, Kamadeen Olawale; LAWAL, Muhideen A. (GeoScience Engineering, 2018)
Building collapse has been a recurrent environmental hazard in Nigeria in the last two decades. This is a corollary of inadequate foundation investigation prior to construction, poor government policies, and general lack of awareness on the importance of geophysical and geotechnical investigations. In this study, geological mapping and detailed geophysical investigation using Electrical Resistivity Imaging (ERI) and Vertical Electrical Sounding (VES) were carried out to understand the suitability of proposed building sites at the main campus of the Olabisi Onabanjo University (OOU), Ago-Iwoye, Nigeria for construction. Both Wenner array and dipole-dipole were used for profiling and Schlumberger for sounding. Four transverses and VES were used in each of the three areas investigated. Our results show that the subsurface of the study areas is underlain by Precambrian basement rock of Nigeria. Rocks in the study area include banded gneiss, porphyroblastic gneiss, biotite-hornblende granite, and quartzite schist. The sounding stations across the three areas and 2D resistivity imaging revealed three principal geoelectric layers, the topsoil, the weathered layer and the fractured/fresh basement with varied resistivity values for each layer. At the VES stations, the three geoelectric layers have resistivity values of 62 to 1182 Ωm, 3.2 to 1360Ωm and 87 to 4680 Ωm. On the 2D resistivity imaging profiles, the resistivity of the three layers varies from 2 to 1182 Ωm, 30to 1360 Ωm, and 40 to 2904 Ωm for the topsoil, the weathered basement, and fractured/fresh bedrock. Our work demonstrates that some of the proposed sites are structurally incompetent for engineering or foundation purposes. Excavation of the topsoil and reinforcement are required to sustain the proposed structures. Keywords: Subsurface, Resistivity, Foundation, Failure, Site investigation https://doi.org/10.2478/gse-2018-0013